Reflexões sobre a implantação de um Laboratório Interativo de Matemática (LIM): Limitações, inovações e contribuições - Amaral, Dhiego Vieira do (2016)
The present work aims to present a research developed about the Interactive Laboratory of Mathematics (LIM), which was a donation from the State Government of Paraíba to most of the schools of the state network. In our research, we will try to identify if the LIM and the way it was inserted in the schools is convergent to what the literature presents about the implantation and use of the Laboratory of Mathematics Teaching (LEM) in the educational institutions, besides investigating in parallel the contribution that The same can give the teacher in the development of his work. Thus, we developed our investigative activity through the LIM, verifying and evaluating the use of the same in a high school class (2nd year). Our work is based on research already published, where we identified that the use of the Mathematics Teaching Laboratory (LEM) in mathematics classes is being encouraged. Among these scholars are: Silva (2012), Lorenzato (2006, 2010), Turrione (2004), Ferronato (2012), among others. In addition, we seek to make a discussion about the new reality and challenges that the teaching work has faced. This study is of a qualitative nature, in which I was a researcher in a teacher's classroom. Among the results obtained, we observed thet the LIM is not in agreement with what the literature presentes about the implantion and use of the Mathematics Laboratory in the school. In addition, the way in which it was implanted can misconceptions about the LEM.